INCONTROLABLE AND TEMPORALITY IN RUSSIAN AND FRENCH - S. Tulanov (Galaxy International Interdisciplinary Research Journal, 2022)
In this article, we discuss how semantics influences uncontrollable verb usage in a temporary form. We will see the work of linguists who are researching this theme.